<span><span>13−<span>6x</span></span>=<span><span><span>(<span><span>2x</span>−5</span>)</span>2</span>+3</span></span>Step 1: Simplify both sides of the equation.<span><span><span>−<span>6x</span></span>+13</span>=<span><span><span>4<span>x2</span></span>−<span>20x</span></span>+28</span></span>Step 2: Subtract 4x^2-20x+28 from both sides.<span><span><span><span>−<span>6x</span></span>+13</span>−<span>(<span><span><span>4<span>x2</span></span>−<span>20x</span></span>+28</span>)</span></span>=<span><span><span><span>4<span>x2</span></span>−<span>20x</span></span>+28</span>−<span>(<span><span><span>4<span>x2</span></span>−<span>20x</span></span>+28</span>)</span></span></span><span><span><span><span>−<span>4<span>x2</span></span></span>+<span>14x</span></span>−15</span>=0</span>Step 3: Use quadratic formula with a=-4, b=14, c=-15.<span>x=<span><span><span>−b</span>±<span>√<span><span>b2</span>−<span><span>4a</span>c</span></span></span></span><span>2a</span></span></span><span>x=<span><span><span>−<span>(14)</span></span>±<span>√<span><span><span>(14)</span>2</span>−<span><span>4<span>(<span>−4</span>)</span></span><span>(<span>−15</span>)</span></span></span></span></span><span>2<span>(<span>−4</span>)</span></span></span></span><span>x=<span><span><span>−14</span>±<span>√<span>−44</span></span></span><span>−<span>8</span></span></span></span>
Answer:
Fourth Quadrant
Step-by-step explanation:
a>0 = a is a positive number = +y
b<0 = b is a negative number = -x
[-b,-a] = [-(-x), -(+y)] = [x, -y]
[positive, negative] is on the fourth quadrant
Answer:
Sum is - 5n² -8n + 4.
Step-by-step explanation:
Given : (3n² – 5n + 6) + (–8n²– 3n – 2) .
To find : Sum .
Solution : We have (3n² – 5n + 6) + (–8n²– 3n – 2) .
Combine like terms :
(3n² - 8n²– 5n - 3n + 6 - 2).
- 5n² -8n + 4.
Therefore, Sum is - 5n² -8n + 4.
Answer:
there is no photo
Step-by-step explanation: